Một phương pháp xây dựng hệ soạn thảo và phân tích công thức toán học - Khang, Tran Dinh; Kiem, Hoang (Journal of Computer Science and Cybernetics, 2018)
This paper presents a method for improving intelligent interfaces – a graphics editor and an accompanied recognizer subsystem to transform the symbolic expressions, formular,… obtained from that editor into a calculating procedure on real-time. Our method is used in designing and implementing a toolbox for calculating nonprogrammable.